Tree shelters facilitate brown oak seedling survival and establishment in a grazing‐dominant forest of Bhutan, Eastern Himalaya. Issue 5 (9th August 2020) - Dorji, Tshewang; Facelli, José M.; Norbu, Tshewang; Delean, Steven; Brookes, Justin D.
Abstract : Brown oak ( Quercus semecarpifolia ) forest is essential for ecological and socioeconomic functions, mainly grazing in the Himalayas. The tree has failed to regenerate naturally and is a threatened species. Restoration of brown oaks is crucial to ensure sustainability while maintaining livestock grazing in these habitats. Achieving this requires cost‐effective restoration techniques that are practicable and sympathetic to the multiple uses of the forest. We assessed the combined effect of grazing (control) and three tree shelters (Protex tubes, mesh wires, and wooden frames) on the field performance of oak seedlings in a forest with heavy grazing pressure. Seedling survival and morphological indicators, including seedling height, collar diameter, sturdiness quotient (SQ), and leaf mass per area (LMA) indices, were measured. More than 90% of control seedlings without protective shelters suffered severe browsing and demonstrated significantly lower survival rates compared to tree shelter seedlings, indicating that grazing was the primary factor governing regeneration success. Seedling survival in tree shelters was three times higher, while the height increase was two times higher than the control. Additionally, locally made mesh wire and wooden tree shelters were more effective than Protex and control in producing quality seedlings reflected by the SQ and LMA values. We suggest that tree shelter is a promising option to restore brown oaks due to its efficacy to defend grazing and support the local community's rights to forest grazing. Our finding is expected to support Bhutan's forest policy of incorporating grazing and tree regeneration into forest management.